Barriers to obtaining prostate multi‐parametric magnetic resonance imaging in African‐American men on active surveillance for prostate cancer. (21st May 2019) - Walton, Eric L.; Deebajah, Mustafa; Keeley, Jacob; Fakhouri, Shadi; Yaguchi, Grace; Pantelic, Milan; Rogers, Craig; Park, Hakmin; Menon, Mani; Peabody, James O.; Dabaja, Ali; Alanee, Shaheen
Abstract: Purpose: Magnetic resonance imaging is playing an ever‐bigger role in the management of prostate cancer. This study investigated barriers to obtaining multi‐parametric MRI (mpMRI) in African‐American men on active surveillance for prostate cancer in comparison to white men affected by the same type of cancer. Materials and Methods: Retrospective review of prostate mpMRI orders from August 2015 to October 2017 at a single health organization treating a diverse population was performed. Data was extracted from the electronic medical records and cancellations were examined based on the documented reason for mpMRI cancellation, race, median zip code household income, and distance from healthcare facility. Results: Out of 793 prostate mpMRI orders, 201 (25%) went unscanned. Access to care issues accounted for 46% of unscanned orders. Patient cancellations were the most common, followed by difficulty contacting patients, and insurance denials. African‐American patients disproportionately went unscanned because institution staff were unable to contact patients (29% vs 10% in white men, P  = 0.0015). Median zip code household income was significantly different between racial groups but did not vary between indication for cancellation. Conclusions: African‐American prostate cancer patients' access to mpMRI is hindered more by barriers to care than White patients. Urology providers must consider these issues before using prostate mpMRI within their active surveillance pathways. Abstract : Access to care issues accounted for 46% of unscanned patients treated for prostate cancer. Patient cancellations followed by difficulty contacting patients, and insurance denials are the most common causes for not undergoing magnetic resonance imaging in patients with prostate cancer. African‐American patients disproportionately went unscanned because institution staff were unable to contact patients.